ROLE OF INTEGRITY IN ENHANCING EFFECTIVE PROCUREMENT PRACTICE IN KENYA BUREAU OF STANDARDS - Obura, Collins Ochieng (European Journal of Business and Strategic Management, 2019)
Purpose: Integrity risks occur in every stage of the procurement process, from the needs assessment over the biding phase to the contract execution and payment. These risks includes duplication of invoicing for goods and services not supplied and abuse of non-competitive procedures on the basis of legal exceptions such as contract splitting, abuse of extreme urgency, and non-supported modifications. There is therefore a genuine demand for public sector institutions to strengthen high integrity in their operations so as to promote good governance and in enhancing sound management of public procurement. This study investigates the role of integrity in enhancing effective procurement practice in Kenya bureau of standards. Methodology: A case study design was adopted and a random stratified sampling method was used to select sample size from the target population. The target population for this study included Executives, procurement officers, and Quality Officers of Kenya Bureau of standards. This study used a random stratified sampling method to select a sample from the population and arrived to a total of 28 respondents as the sample size. The study used a questionnaire to collect primary data. The researcher used both qualitative and quantitative techniques in analyzing the data. Descriptive analysis such as mean, frequencies and percentages was used to analyze the data. The study used the following regression model. Results: The study findings revealed that relationship between buyer and supplier plays an important role in effective procurement practice, and that, poor business relationship promote bad image to the organization. Transparency and accountability were found to be important in procurement and plays a significant role in ensuring effective public procurement practice. The study findings also revealed that risk management is useful in all public procurement projects. Unique Contribution to Theory, Practice and Policy: The study recommends that Rules and norms that promote integrity in an organization should be adopted by management and embraced by employees. Developing competent integrity promotes good image to an organization hence attracting reliable business partners that offers a completely different set of services to a market that is similar to its own, allowing the business to increase its market size with little impact on the franchise business